2010
DOI: 10.1016/j.jmb.2010.04.065
|View full text |Cite
|
Sign up to set email alerts
|

The Macroscopic Rate of Nucleic Acid Translocation by Hepatitis C Virus Helicase NS3h Is Dependent on Both Sugar and Base Moieties

Abstract: The NS3 helicase (NS3h) of hepatitis C virus (HCV) is a 3′ to 5′ SF2 RNA and DNA helicase that is essential for the replication of HCV. We have examined the kinetic mechanism of translocation of NS3h along single-stranded nucleic acid with bases rU, dU and dT and have found that the macroscopic rate of translocation is dependent upon both the base and sugar moieties of the nucleic acid, with approximate macroscopic translocation rates of 3 nt/s (oligo-dT), 35 nt/s (oligo-dU), and 42 nt/s (oligo-rU), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
50
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 49 publications
8
50
2
Order By: Relevance
“…Interestingly, the affinity of NS3h for binding these translocation substrates is inversely proportional to the associated macroscopic rate of translocation (71), similar to what has been observed for the Rep helicase (51). This suggests that the efficiency with which NS3h can couple ATP binding and hydrolysis to nucleic acid translocation provides a constraint that results in a compensatory relationship between the affinity of nucleic acid binding and the macroscopic rate of nucleic acid translocation (71).…”
Section: Sf2 Family Helicasessupporting
confidence: 80%
See 4 more Smart Citations
“…Interestingly, the affinity of NS3h for binding these translocation substrates is inversely proportional to the associated macroscopic rate of translocation (71), similar to what has been observed for the Rep helicase (51). This suggests that the efficiency with which NS3h can couple ATP binding and hydrolysis to nucleic acid translocation provides a constraint that results in a compensatory relationship between the affinity of nucleic acid binding and the macroscopic rate of nucleic acid translocation (71).…”
Section: Sf2 Family Helicasessupporting
confidence: 80%
“…Further confirmation of the correlation between substrate binding affinity and DNA translocation is found in a separate study in which a macroscopic rate of (46 ± 5) nt/s for NS3h translocation along oligo(dT) was determined at higher temperature and higher NaCl concentration (72); an increase in both the temperature and the NaCl concentration would likely decrease the affinity of ssDNA binding by NS3h. This comparison is made slightly problematic, however, by the fact that these two studies used different constructs for NS3h (71,72). Nevertheless, it is worth mentioning that both studies reported similar estimates of the kinetic stepsize of translocation along oligo(dT) [(1.38 ± 0.07) nt (71) vs. (1.7 ± 0.2) nt (72)] and that an additional slow process occurs during the translocation mechanism (71,72).…”
Section: Sf2 Family Helicasesmentioning
confidence: 99%
See 3 more Smart Citations